Utilisation of essential oils as a natural growth promoter for broiler chickens. Issue 1 (2nd January 2019) - Attia, Youssef; Al-Harthi, Mohammed; El-Kelawy, Mahmoud
Abstract: This study assessed the impacts of essential oils (EOs) consisting of 4.5 g cinnamaldehyde and 13.5 g thymol per 100 g of EOs as phytogenic growth promoters in broiler diet. A total of 216, one-day-old male Arbor Acres broiler chickens were randomly allotted into six groups, each with six replicates. The 1st group was fed a basal diet (Control) without supplementation; the 2nd group was fed the basal diet including zinc bacitracin (ZnB); the 3rd, 4th, 5th and 6th groups were fed the basal diet including EOs at 25 (EOs_25), 50 (EOs_50), 100 (EOs_100) and 150 (EOs_150) mg/kg diet, respectively. The group EOs_150 showed significantly increased ( p < .05) body weight gain (BWG), enhanced feed conversion rate (FCR) and production efficiency index (PEI) compared to the other groups, except for EOs_100. Increasing concentrations of EOs above 25 mg/kg significantly ( p < .05) increased protein, lipid and fibre digestibility; the addition of EOs also increased the amount of edible parts and dressing percentage of carcases. Diets EOs_100 and EOs_150 resulted in significantly increased plasma total protein and globulin levels, while EOs_150 led to higher plasma glucose concentrations. From the findings, supplementation with 100 mg/kg EOs in encapsulated, heat-stable forms could be used as an alternative growth promoter to ZnB in broiler chickens. Highlight: Essential oils can replace antibiotic in broiler nutrition with no adverse effects on growth performance. Essential oils improved total edible parts and dressing percentage. Essential oils enhanced digestibility of protein, lipid and fibre. Thus essential oils contained of 4.5 g cinnamaldehyde and 13.5 g thymol per 100 g can be used at 100 mg/kg feed as alternative growth promoter for broilers chickens.